Dual-Action Botanicals: Antiviral and Insecticidal Potential of Bangladeshi Medicinal Plants against Aedes-Borne Viruses - Sarwar, A K M Golam (Journal of the Bangladesh Agricultural University, 2025)
Medicinal and aromatic plants (MAPs) have been utilized in the Indian subcontinent to combat viral infections and insect vectors since prehistoric times. This study examines the application of Bangladeshi MAPs for the treatment of Zika virus (ZIKV). It also provides a comprehensive review of prevention and management strategies for diseases transmitted by Aedes mosquitoes. A total of sixty-two Bangladeshi MAPs, belonging to 59 genera and 36 families, exhibit potential antiviral properties against ZIKV. Among these, four species, viz., Erythroxylum sp., Chamaecrista sp., Scleromitrion diffusum, and Camellia sinensis, demonstrated activity against chikungunya virus (CHIKV). Additionally, four species, Allium sativum, Tridax procumbens, Trigonella foenum-graecum, and Punica granatum, showed effectiveness against dengue virus (DENV). Nine other species, including Andrographis paniculata, Azadirachta indica, Curcuma longa, Glycyrrhiza glabra, Ocimum tenuiflorum, Psidium guajava, Tinospora cordifolia, Vitex negundo, and Zingiber officinale, were found to reduce viral loads of all three viruses, DENV, CHIKV, and ZIKV, transmitted by Aedes mosquitoes. Furthermore, at least sixteen species, including Andrographis paniculata, Azadirachta indica, Bixa orellana, Blumea balsamifera, Camellia sinensis, Cannabis sativa, Cinnamomum verum, Curcuma longa, Momordica charantia, Psidium guajava, Rauvolfia serpentina, Tecoma stans, Tridax procumbens, Piper nigrum, Vitex negundo, and Zanthoxylum nitidum, exhibited both antiviral and insecticidal properties against Aedes spp. Also, Allium sativum, Kaempferia galanga, Lippia alba, and Zingiber officinale were effective against both Aedes spp. and Culex quinquefasciatus. At the same time, Punica granatum showed efficacy against A. aegypti, Anopheles stephensi, and C. quinquefasciatus. This study underscores the significance of integrating traditional knowledge with contemporary scientific methods to develop innovative plant-based therapeutics and environmentally friendly insecticides. J Bangladesh Agril Univ 23(4): 508–515, 2025